If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(80 + -1x) + -1x * 3 + -1x = 0 (80 * 2 + -1x * 2) + -1x * 3 + -1x = 0 (160 + -2x) + -1x * 3 + -1x = 0 Reorder the terms for easier multiplication: 160 + -2x + -1 * 3x + -1x = 0 Multiply -1 * 3 160 + -2x + -3x + -1x = 0 Combine like terms: -2x + -3x = -5x 160 + -5x + -1x = 0 Combine like terms: -5x + -1x = -6x 160 + -6x = 0 Solving 160 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-160' to each side of the equation. 160 + -160 + -6x = 0 + -160 Combine like terms: 160 + -160 = 0 0 + -6x = 0 + -160 -6x = 0 + -160 Combine like terms: 0 + -160 = -160 -6x = -160 Divide each side by '-6'. x = 26.66666667 Simplifying x = 26.66666667
| 6(y-7)+4y=8 | | -35n=-105 | | x-y+20=0 | | p-10=29 | | 3w+2=64 | | -5n=-105 | | 3w+x-2=64 | | -5x-8y=60 | | -2x+4x=-3x+x-20 | | .2(100000+x)=28000 | | 3w-2=64 | | (80-x)+(2x-x)+(3x-x)=0 | | .01x= | | 41=12d+7 | | 4t^2-8t+6=0 | | Y^2=x^2+25 | | y=ln(5)-ln(3) | | -8+8x=6x+18 | | 3x+7=34+1 | | a/8=3 | | 3x+7=34-28 | | 0=-6x^2+x^3 | | 10/13=m/11 | | 3x+7=34-28+15 | | -22-5x=38-x | | 0=-x^2+6x-2 | | z=hw-hw^2 | | 208500000000+5550000x=3056890000-15000000x | | 5x-47=68+10x | | 4y+15=105 | | 3(x+9)=6 | | (2/3-1/2)×4/9 |